CD40-targeted dendritic cell delivery of PLGA-nanoparticle vaccines induce potent anti-tumor responses. (February 2015) - Rosalia, Rodney A.; Cruz, Luis J.; van Duikeren, Suzanne; Tromp, Angelino T.; Silva, Ana L.; Jiskoot, Wim; de Gruijl, Tanja; Löwik, Clemens; Oostendorp, Jaap; van der Burg, Sjoerd H.; Ossendorp, Ferry
Abstract: Dendritic cells (DC) play a prominent role in the priming of CD8 + T cells. Vaccination is a promising treatment to boost tumor-specific CD8 + T cells which is crucially dependent on adequate delivery of the vaccine to DC. Upon subcutaneous (s.c.) injection, only a small fraction of the vaccine is delivered to DC whereas the majority is cleared by the body or engulfed by other immune cells. To overcome this, we studied vaccine delivery to DC via CD40-targeting using a multi-compound particulate vaccine with the aim to induce potent CD8 + T cell responses. To this end, biodegradable poly(lactic-co-glycolic acid) nanoparticles (NP) were formulated encapsulating a protein Ag, Pam3CSK4 and Poly(I:C) and coated with an agonistic αCD40-mAb ( NP-CD40 ). Targeting NP to CD40 led to very efficient and selective delivery to DC in vivo upon s.c. injection and improved priming of CD8 + T cells against two independent tumor associated Ag. Therapeutic application of NP-CD40 enhanced tumor control and prolonged survival of tumor-bearing mice. We conclude that CD40-mediated delivery to DC of NP-vaccines, co-encapsulating Ag and adjuvants, efficiently drives specific T cell responses, and therefore, is an attractive method to improve the efficacy of protein based cancer vaccines undergoing clinical testing in the clinic.